2000
DOI: 10.1139/g00-034
|View full text |Cite
|
Sign up to set email alerts
|

Identification of DNA polymorphism in cultivated groundnut using random amplified polymorphic DNA (RAPD) assay

Abstract: Construction of a genetic linkage map is necessary to apply marker-assisted selection tools in a crop improvement program. Except for the recent studies from two laboratories, most of the previous studies have shown little or no DNA polymorphism in cultivated groundnut (Arachis hypogaea L.). In the present study, 70 selected genotypes, representing variability for several morphological, physiological, and other characters, were studied for polymorphism employing random amplified polymorphic DNA (RAPD) assay wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
48
3
3

Year Published

2004
2004
2022
2022

Publication Types

Select...
3
2
2

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 19 publications
(23 reference statements)
4
48
3
3
Order By: Relevance
“…Cultivars S 230 and Spanish Improved derived as selections from germplasm were in different group as per quantitative traits, but at genetic level they were similar. As observed in the present study also very low diversity among cultivars at genetic level have been reported by using RAPD (Subramanian et al, 2000 ;Dwivedi et al, 2001), AFLP (Herselman, 2003) and SSR (Raina et al, 2001;Krishna et al, 2004) markers.…”
Section: Morphological Vs Molecular Diversitysupporting
confidence: 53%
See 1 more Smart Citation
“…Cultivars S 230 and Spanish Improved derived as selections from germplasm were in different group as per quantitative traits, but at genetic level they were similar. As observed in the present study also very low diversity among cultivars at genetic level have been reported by using RAPD (Subramanian et al, 2000 ;Dwivedi et al, 2001), AFLP (Herselman, 2003) and SSR (Raina et al, 2001;Krishna et al, 2004) markers.…”
Section: Morphological Vs Molecular Diversitysupporting
confidence: 53%
“…Banding pattern of seventeen genotypes is presented in Figure 5. High polymorphism observed among the cultivars may be due to use of reported polymorphic primers (Subramanian et al, 2000;Dwivedi et al, 2001;Rajendraprasad, 2003;Vijay, 2003;Nagaraja Reddy et al, 2004;Pattanashetti, 2005). In contrast, Dwivedi et al, 2001 have reported low to moderate level of polymorphism ranging from 8.7 to 33.1 per cent among primers in twenty-six accessions including interspecific derivatives, land races and released cultivars.…”
Section: Molecular Diversitymentioning
confidence: 99%
“…This would compliment classical breeding programmes and provide the basis for map-based cloning for groundnut rosette resistance genes. However, results throughout the world (Grieshammer and Wynne 1990;Halward et al 1991;He and Prakash 1997;Hopkins et al 1999;Subramanian et al 2000;Herselman 2003) have indicated that molecular work on cultivated peanut presents a significant challenge due to its inherent narrow genetic base.…”
Section: Introductionmentioning
confidence: 99%
“…The first studies were based on isozymes and proteins (Krishna and Mitra 1988;Grieshammer and Wynne 1990;Lu and Pickersgill 1993), followed by Restriction Fragment Length Polymorphism-RFLPs Paik-Ro et al 1992;Kochert et al 1996), Random Amplified Polymorphic DNARAPDs (Halward et al , 1992Hilu and Stalker 1995;Subramanian et al 2000), Amplified Fragment Length Polymorphism-AFLPs (He and Prakash, 1997;Gimenes et al 2000;He and Prakash 2001;Gimenes et al 2002;Herselman, 2003;Milla et al 2005aMilla et al , 2005bTallury et al 2005), and more recently microsatellite markers (Hopkins et al 1999;Palmieri et al 2002;He et al 2003;Ferguson et al 2004;Moretzsohn et al 2004;He et al 2005;Moretzsohn et al 2005;Palmieri et al 2005;Bravo et al 2006;Budiman et al 2006;Gimenes et al 2007;Proite et al 2007;Wang et al 2007;Cuc et al 2008;Naito et al 2008;Liang et al 2009;Moretzsohn et al 2009;Song et al 2010;Yuan et al 2010;Koilkonda et al 2012;Macedo et al 2012;Pandey et al 2012) and...…”
Section: Molecular Markers For Arachismentioning
confidence: 99%
“…Screening of isozyme, RFLP, and RAPD markers on accessions of A. hypogaea identified only very low levels of polymorphism among cultivated peanut accessions Halward et al 1992;Lu and Pickersgill 1993;Burow et al 1996;Subramanian et al 2000;Dwivedi et al 2001). The partial first linkage map from a cross between accessions of A. hypogaea was constructed using an F 2 population (Herselman et al 2004).…”
Section: Genetic Maps Based On Cultivated X Cultivated Crossesmentioning
confidence: 99%